2016
DOI: 10.1002/piq.21220
|View full text |Cite
|
Sign up to set email alerts
|

Examining Instructional Design Principles Applied by Experienced Designers in Practice

Abstract: There has been ongoing debate regarding the efficacy of teaching instructional design models to novice designers given that experienced instructional designers often use principles and adapted models when they engage in the instructional design problem‐solving process. This study utilized the Delphi technique to identify a core set of guiding principles used by designers in their practice. The purpose of this study was (1) to examine and describe the principles that guided instructional designers’ practice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The authors of [ 10 , 11 ] have highlighted how IDs should learn; they conclude that learning should include a variety of methods, including studio- and practice-based activities as opposed to more typical classroom-based methods. The authors of [ 12 ] studied skilled IDs and found unanimity on 61 ID principles; 32 of the 61 design principles fit the ADDIE framework, including understanding your students and target audience, using the best technology, and piloting, if feasible. The remaining 29 principles include communication, client management, and project management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [ 10 , 11 ] have highlighted how IDs should learn; they conclude that learning should include a variety of methods, including studio- and practice-based activities as opposed to more typical classroom-based methods. The authors of [ 12 ] studied skilled IDs and found unanimity on 61 ID principles; 32 of the 61 design principles fit the ADDIE framework, including understanding your students and target audience, using the best technology, and piloting, if feasible. The remaining 29 principles include communication, client management, and project management.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 29 principles include communication, client management, and project management. The authors of [ 12 ] suggest that this could have a number of effects on the field of ID. IDs could undertake either case-based learning [ 13 , 14 ] or real-world problem solving to go beyond the model and cover the full range of principles mentioned above [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…1.4 Rationales Documenting how instructional designers spend their time is beneficial to the field for several reasons (Cox & Osguthorpe, 2003). First, past research suggested a mismatch between theory and practice (Ashbaugh, 2013;York & Ertmer, 2016). This mismatch may be due to models being built around a theoretical, or otherwise limited, view of instructional design practice (Gray et al, 2015).…”
Section: Topics Of Inquirymentioning
confidence: 99%
“…Where the research is lacking is in providing a holistic view of what it is exactly that instructional designers do and how they do it (Sugar, 2014). While the research community seems to be aware of and working toward addressing this gap, the refrain referencing the void is still common (Boling et al, 2017;Cox & Osguthorpe, 2003;Rowland, 1992;Stefaniak et al, 2018;Sugar, 2014;York & Ertmer, 2016). There are multiple challenges facing researchers, however.…”
mentioning
confidence: 99%
See 1 more Smart Citation